2020
DOI: 10.1186/s12935-020-01517-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between TRAF6 and tumors

Abstract: Tumor necrosis factor receptor (TNFR)-related factors (TRAFs) are important linker molecules in the tumor necrosis factor superfamily (TNFSF) and the Toll-like/interleukin-1 receptor (TLR/ILR) superfamily. There are seven members: TRAF1-TRAF7, among those members, tumor necrosis factor receptor-associated factor 6 (TRAF6) is upregulated in various tumors, which has been related to tumorigenesis and development. With the in-depth study of the relationship between TRAF6 and different types of tumors, TRAF6 has o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 121 publications
(153 reference statements)
1
42
0
Order By: Relevance
“…In human cancers, genetic changes in the gain and loss of function of different tumor necrosis factor receptor-associated factors (TRAFs) are common [ 19 ]. TRAF6 is the abundantly expressed gene that relates to tumorigenesis and development [ 20 ]. In fact, TRAF6 is the regulatory actor in liver cancer, as to cell apoptosis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In human cancers, genetic changes in the gain and loss of function of different tumor necrosis factor receptor-associated factors (TRAFs) are common [ 19 ]. TRAF6 is the abundantly expressed gene that relates to tumorigenesis and development [ 20 ]. In fact, TRAF6 is the regulatory actor in liver cancer, as to cell apoptosis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that enhancement of TRAF6 expression in obesity could increase degradation of EZH2, thereby promoting upregulation of miR-429-3p. In addition, TRAF6 also plays a critical role in the activation of nuclear transcription factors associated with adipogenesis and obesity, such as NF-ÎșB and AP-1 [48,49]. In silico analysis of transcription factor binding sites showed that the promoter regions of miR-429-3p contain tentative binding sites for NF-ÎșB and AP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the dichotomy between ubiquitination and phosphorylation might underlie the differential functions of P-bodies, where phosphorylation favors mRNA storage and ubiquitination favors decay. These PTMs depend on the E3 ubiquitin ligase TRAF6 [117], which is overexpressed in many cancer types and is associated with poor prognosis [118].…”
Section: Box 1 Rnp Granule Functions Beyond Cancer Cellsmentioning
confidence: 99%